Y - 4 = - (1)/(4) (x-0) I came up with: -4y + 16 = X I continued to Standard form (Ax+Bx=C); X-4y=16 book has: 4y-16 = -X X + 4y = 16

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Y - 4 = - (1)/(4) (x-0) I came up with: -4y + 16 = X I continued to Standard form (Ax+Bx=C); X-4y=16 book has: 4y-16 = -X X + 4y = 16

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Your first solution (\(-4y + 16 = X\)) is the same as theirs, they just chose to leave the negative sign on the X. Your second solution has a slight sign error -- you move the 16 over to the right and then the X to the left (here it is done with both their form of the equation and yours): \[\begin{align} 4y - 16 &= -x & -4y + 16 &= x \\4y + x &= 16 & -4y - x &= -16 \\x + 4y &= 16 & 4y + x &= 16 \end{align}\]

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Not the answer you are looking for?

Search for more explanations.

Ask your own question